Lattice oxygen regulation type nano-catalyst as well as preparation method and application thereof

By using a lattice oxygen regulatory nano -catalyst, the problem of incomplete degradation of mud ethical polymers in existing technologies has been solved, and the deep cracking of sludge and high -efficiency oxidation of organic matter can be used. Resource use.

CN119346118APending Publication Date: 2025-01-24HANGZHOU SHENRUI WATER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411477415.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing hydrothermal oxidation technology cannot effectively degrade extracellular polymers in the sludge, resulting in the bottom sludge treated with sludge still containing a high amount of organic matter and the carbon source recovery is not thorough.

Method used

The catalyst is composed of the catalyst and the active nano metal (RU or Ni) of the regulatable carrier (composite oxide of TiO2 and ZRO2) and active nano -metal (RU or NI). Precise regulation of proportion.

Benefits of technology

It significantly increased the degree of degradation of the extracellular polymer of the sludge, so that more organic matter in the sludge was released into the liquid phase, and the sludge cracked more thoroughly. Easy to use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346118A_ABST
    Figure CN119346118A_ABST
Patent Text Reader

Abstract

The invention discloses a lattice oxygen regulation type nano-catalyst as well as a preparation method and application thereof. The catalyst comprises a carrier and active nano-metal, wherein the ratio of lattice oxygen to defect oxygen can be regulated; the carrier is a TiO2 and ZrO2 composite oxide with an adjustable lattice oxygen ratio; and the active nano metal is selected from any one of Ru and Ni active metal nano particles. Metal active sites and oxygen species on the surface of the catalyst can enhance cracking of extracellular polymeric substances of the sludge and release of organic matters in the sludge, deep cracking of the sludge is realized, and the selectivity of organic matter carboxylic acid products is improved; rich active metal sites on the surface of the catalyst are matched with active nano metal particles to accelerate generation of free radicals, the reaction efficiency is improved, interaction between precursor surface compounds formed by reactants on the surface of the catalyst and adjacent active metal sites and defect oxygen is controlled, the oxidation degree is regulated and controlled, and the product selectivity is improved; the catalyst can realize HTO treatment of sludge at 200 DEG C or below, and the treated product can be used as a high-quality carbon source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrothermal oxidation sludge treatment catalysts, and in particular to a lattice oxygen-regulated nanocatalyst and a preparation method and application thereof. Background Art

[0002] The activated sludge method is mainly used in the biological treatment of urban sewage in my country. The mechanism of activated sludge treatment of sewage is as follows: in the sewage treatment process, the bacterial flocs oxidize and decompose various organic matter in the wastewater into carbon dioxide and water, and generate flocs at the same time. At this time, the microbial group of activated sludge is formed. The activated sludge absorbs some pollutants in the sewage and flocculates and settles, producing a large amount of residual sludge.

[0003] Sludge is mainly composed of sludge flocs and water. Sludge flocs are mainly composed of two parts: cell bodies and extracellular polymers. Extracellular polymers are mainly composed of proteins and polysaccharides. Polysaccharide molecules are rich in hydrophilic functional groups such as hydroxyl and carboxyl groups. They can form a stable and elastic network structure through adsorption and bridging, and cross-linking and fixing free cells is beneficial to sludge flocculation. Proteins and lipids can maintain the stability of the floc structure and improve the biological flocculation of sludge accordingly. Polysaccharide molecules, proteins and lipids form a compact and dense network structure through electrostatic forces, hydrogen bonding, ion attraction, biochemistry and other effects, which can serve as a protective layer for microorganisms to resist the invasion of adverse factors such as external heavy metals and toxic compounds. Therefore, the presence of extracellular polymers is also the main reason for the difficulty in sludge degradation. At the same time, the various forces inside / between extracellular polymers make the water in the sludge tightly bound inside / between the sludge flocs through adsorption or chemical bonds, which ultimately leads to a high moisture content in the sludge and is not easy to dehydrate.

[0004] The problem of excess sludge generated during the sewage treatment process is becoming increasingly serious. Excess sludge has a high moisture content, large volume, a foul odor, and contains a large number of pathogens, heavy metals and other toxic substances. Improper treatment can easily cause serious secondary environmental pollution. Traditional sludge treatment technologies include anaerobic digestion, dehydration, landfill, incineration, etc. However, traditional sludge treatment technologies have fatal problems such as high cost and secondary pollution, and cannot realize the resource utilization of sludge.

[0005] Hydrothermal Oxidation (HTO) is widely used in the field of organic wastewater and solid waste treatment due to its green and efficient advantages. The reaction with an oxidant in an aqueous solution under high temperature and high pressure conditions in a closed system is a hydrothermal oxidation reaction. Hydrothermal oxidation conditions can effectively release the water component in the sludge, and at the same time break the cell structure in the sludge, thereby releasing the organic matter in it and dissolving it in the liquid phase, thereby achieving sludge stabilization, harmlessness and reduction. In addition, the released organic matter is dissolved in the supernatant, and a large amount of soluble organic matter is oxidized and degraded into volatile fatty acids VFAs and other organic matter such as carbohydrates and proteins under oxygen-rich conditions, which can be used as substrates for the metabolism of various microorganisms. It is a high-quality carbon source and realizes resource utilization. However, the existing HTO technology cannot effectively degrade the extracellular polymers of the sludge, resulting in a low degree of degradation of the extracellular polymers of the sludge, and thus cannot achieve deep decomposition of the sludge, resulting in a high content of organic matter in the treated sludge and incomplete carbon source recovery. Summary of the invention

[0006] The present invention provides a new lattice oxygen regulated nanocatalyst and a preparation method and application thereof to solve the above problems.

[0007] In order to achieve the above object, the technical solution of the present invention is:

[0008] A lattice oxygen regulated nanocatalyst, comprising a carrier with a regulated ratio of lattice oxygen to defect oxygen and an active nanometal;

[0009] The carrier is TiO with adjustable lattice oxygen ratio 2 and ZrO 2 Composite oxides;

[0010] The active metal is selected from any one of Ru and Ni active metal nanoparticles; the diameter of the active metal nanoparticles is 1.0 to 2.5 nm;

[0011] Furthermore, the active metal loading is 0.5-5wt.%.

[0012] Furthermore, the two oxides TiO 2 and ZrO 2 The mass ratio is 2:8 to 8:2;

[0013] The metal molar ratio of the sum of Ti and Zr in the active nano-metal and the carrier composite oxide is 1:1-20.

[0014] Another aspect of the present invention provides a method for preparing the lattice oxygen-regulated nanocatalyst, comprising the following steps:

[0015] S1: Active nanometal and metal oxide TiO added to the ball mill 2 Nitrates and metal oxides containing ZrO 2 Nitrate, wherein the molar ratio of the sum of the moles of Ti and Zr to the active nano metal is 1 to 20:1; then an auxiliary material is added, and the auxiliary material and the metal oxide TiO 2 Nitrates and metal oxides containing ZrO 2 The mass ratio of the sum of the nitrates is 1 to 2.5:1, and the grinding medium is added in a mass ratio of the grinding medium to the material of 2 to 5:1 for grinding to obtain a viscous slurry;

[0016] S2: drying the viscous slurry obtained in S1 in an oven at 103-105° C. to a constant weight to obtain a dry slurry;

[0017] S3: calcining the dry slurry obtained in S2 in air, and naturally cooling to room temperature after calcination to obtain a lattice oxygen-regulated nanocatalyst.

[0018] Furthermore, the auxiliary material is a solid organic acid.

[0019] Furthermore, in S1, the grinding medium is agate balls, the grinding speed is 200-500 r / min, and the grinding time is 60-180 min.

[0020] Furthermore, in S3, the dried slurry is calcined for 2 to 4 hours at a temperature of 400 to 700°C.

[0021] In another aspect, the present invention provides the use of a lattice oxygen-regulated nanocatalyst described in the above technical solution or a lattice oxygen-regulated nanocatalyst prepared by the preparation method described in the above technical solution in treating sludge to produce carboxylic acid carbon sources.

[0022] Furthermore, the application is carried out in a device for hydrothermal oxidation of excess sludge, the device for hydrothermal oxidation of excess sludge comprising a raw sludge transmission system, a reaction tower, a heat exchange unit and a solid-liquid separation unit connected in sequence; the reaction tower is also connected to a heat supply unit and an air delivery unit, and the heat exchange unit is connected to the heat supply unit;

[0023] The process steps of the application are as follows:

[0024] Firstly, the residual sludge is transported to the reaction tower by using the raw sludge transmission system, and then the lattice oxygen-regulated nanocatalyst is added into the reaction tower, an oxidant is introduced into the reaction tower through an air transport unit, and the reaction tower is heated by using a heat supply unit. The lattice oxygen-regulated nanocatalyst and the residual sludge undergo a hydrothermal oxidation reaction, the residual sludge is broken down and a carboxylic acid carbon source is generated, and a solid-liquid mixture material formed after the hydrothermal oxidation reaction is cooled by a heat exchange unit, and after cooling, the solid-liquid mixture material enters a solid-liquid separation unit for solid-liquid separation, and the separated supernatant and filter cake resources are respectively collected.

[0025] Furthermore, the conditions of the hydrothermal oxidation reaction are: reaction pressure 1.0-5.0 MPa, reaction temperature 140-200°C, volume space velocity 0.5-2.0 h -1 , the oxidant is oxygen in the air.

[0026] The beneficial effects of the present invention are:

[0027] The present invention discloses a lattice oxygen regulated nanocatalyst, which can improve the degree of degradation of extracellular polymers in sludge, release more organic matter in sludge into the sludge liquid phase, and make the sludge decomposition more thorough. At the same time, high product selectivity of organic carboxylic acids C1-C2 and C3-C5 is achieved through the regulation of lattice oxygen. The active metal sites on the catalyst surface are enriched with active nano-metal particles to accelerate the generation of free radicals and improve the reaction efficiency. The grinding method is used to achieve precise regulation of the lattice oxygen ratio of the composite oxide carrier structure and the nano-positioning of active metals on the catalyst surface. The catalyst has a high degree of dispersion, so that the higher the proportion of catalyst lattice oxygen, the lower the proportion of defective oxygen, the higher the selectivity of C3-C5 monoacid products, and the higher the selectivity of C1-C2 monoacid and diacid products, thereby controlling the electron transfer rate between the catalyst and the reactants, and controlling the interaction between the precursor surface complex formed by the reactants on the catalyst surface and the adjacent active metal sites and defective oxygen, further realizing the regulation of the oxidation degree, and ultimately achieving improved product selectivity; the catalyst can achieve sludge HTO treatment below 200°C, and will not produce biologically toxic by-products during the sludge treatment process. The treated sludge is deeply cracked, and the liquid product can be used as a high-quality carbon source. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 A schematic diagram of the structure of a device for treating excess sludge using the catalyst prepared by the present invention;

[0030] Figure 2 It is a structural schematic diagram of a small test device used when treating excess sludge using the catalyst prepared in an embodiment of the present invention.

[0031] In the figure:

[0032] 1. Heat supply unit; 2. Reaction tower; 3. Heat exchange unit; 4. Solid-liquid separation unit; 5. Carbon source conveying pipeline; 6. Mud cake transfer vehicle; 7. Air pipeline; 8. Raw sludge transmission pipeline; 9. Cold water pipeline; 10. Heat circulation pipeline; 11. Heating furnace; 12. Reactor; 13. Heat exchanger; 14. Sample storage tank; 15. Air conveying pipeline; 16. Air pressure valve; 17. Gas flow meter; 18. Temperature measuring device; 19. Sampling pipeline; 20. Exhaust pipeline; 21. Vent pipeline; 22. Electronic scale. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Embodiment 1:

[0035] The lattice oxygen-regulated nanocatalyst Ru@TiZrOx-Ov-1 is prepared by a solid phase grinding method, comprising the following steps:

[0036] S1: Add a certain proportion of metal Ru and TiO into the ball mill 2 Nitrate and ZrO 2 Nitrate (TiZr / Ru molar ratio = 15:1), Ru content is 1wt.%, titanium oxide and zirconium oxide ratio is 50%:50%, and auxiliary material citric acid is added at the same time. 2 Nitrate and ZrO 2 The mass ratio of the sum of the nitrates is 1:1. After adding the above materials, agate balls as grinding media are added, and the mass ratio of the grinding media to the materials is 4:1. The above mixture is ground at a grinding speed of 300 r / min for 120 min to obtain a viscous slurry;

[0037] S2: drying the above viscous slurry in an oven at 103-105° C. to constant weight to obtain a dry slurry;

[0038] S3: The dried slurry was calcined in air for 3 hours at a calcination temperature of 400°C. After calcination, it was naturally cooled to room temperature to obtain Ru@TiZrOx-Ov-1 lattice oxygen-regulated nanocatalyst. The electron microscopy results showed that the average diameter of the active metal nanoparticles was 2.0nm. XPS detection of the catalyst O1S showed that the proportion of lattice oxygen on the catalyst surface was greater than the proportion of defective oxygen. The deconvolution calculation results of the O1s XPS peak showed that lattice oxygen accounted for 56.7%, defective oxygen accounted for 36.5%, and the remaining 6.8% were oxygen-containing functional groups on the catalyst surface.

[0039] Embodiment 2:

[0040] The lattice oxygen-regulated nanocatalyst Ru@TiZrOx-Ov-2 is prepared by solid phase grinding method, which includes the following steps:

[0041] S1: Add a certain proportion of metal Ru and TiO into the ball mill 2 Nitrate and ZrO 2 Nitrate (TiZr / Ru molar ratio = 15:1), Ru content is 1wt.%, titanium oxide and zirconium oxide ratio is 75%:25%, and auxiliary material citric acid is added at the same time. 2 Nitrate and ZrO 2 The mass ratio of the sum of the nitrates is 1:1. After adding the above materials, agate balls as grinding media are added to the ball mill, and the mass ratio of the grinding media to the materials is 4:1. The above mixture is ground at a grinding speed of 300 r / min for 120 min to obtain a viscous slurry;

[0042] S2: drying the above viscous slurry in an oven at 103-105° C. to constant weight to obtain a dry slurry;

[0043] S3: The dried slurry was calcined in air for 3 hours at a calcination temperature of 550°C. After calcination, it was naturally cooled to room temperature to obtain Ru@TiZrOx-Ov-2 lattice oxygen-regulated nanocatalyst. The electron microscopy results showed that the average diameter of the active metal nanoparticles was 1.5nm. XPS detection of the catalyst O1S showed that the proportion of lattice oxygen on the catalyst surface was approximately equal to the proportion of defective oxygen. The deconvolution calculation results of the O1s XPS peak showed that the lattice oxygen accounted for 49.0%, the defective oxygen accounted for 40.2%, and the remaining 10.8% were oxygen-containing functional groups on the catalyst surface.

[0044] Embodiment 3:

[0045] The lattice oxygen-regulated nanocatalyst Ru@TiZrOx-Ov-3 is prepared by solid phase grinding method, which includes the following steps:

[0046] S1: Add a certain proportion of metal Ru and TiO into the ball mill 2 Nitrate and ZrO 2 Nitrate (TiZr / Ru molar ratio = 10:1), Ru content is 2.0wt.%, titanium oxide and zirconium oxide ratio is 25%:75%, and auxiliary material citric acid is added at the same time. 2 Nitrate and ZrO 2 The mass ratio of the sum of the nitrates is 2:1. After adding the above materials, agate balls as grinding media are added, and the mass ratio of the grinding media to the materials is 4:1. The above mixture is ground at a grinding speed of 500 r / min for 120 min to obtain a viscous slurry;

[0047] S2: drying the above viscous slurry in an oven at 103-105° C. to constant weight to obtain a dry slurry;

[0048] S3: The dried slurry was calcined in air for 4 hours at a calcination temperature of 700°C. After calcination, it was naturally cooled to room temperature to obtain Ru@TiZrOx-Ov-3 lattice oxygen-regulated nanocatalyst. The electron microscopy results showed that the average diameter of the active metal nanoparticles was 2.5nm. XPS detection of the catalyst O1S showed that the proportion of lattice oxygen on the catalyst surface was less than the proportion of defective oxygen. The deconvolution calculation results of the O1s XPS peak showed that lattice oxygen accounted for 57.2%, defective oxygen accounted for 31.6%, and the remaining 11.2% were oxygen-containing functional groups on the catalyst surface.

[0049] Example 4

[0050] The lattice oxygen-regulated nanocatalyst Ru@TiZrOx-Ov-4 is prepared by solid phase grinding method, which includes the following steps:

[0051] S1: Add a certain proportion of metal Ru and TiO into the ball mill 2 Nitrate and ZrO 2 Nitrate (TiZr / Ru molar ratio = 20:1), Ru content is 0.5wt.%, titanium oxide and zirconium oxide ratio is 50%:50%, and auxiliary material citric acid is added at the same time. 2 Nitrate and ZrO 2 The mass ratio of the sum of the nitrates is 1:1. After adding the above materials, agate balls as grinding media are added, and the mass ratio of the grinding media to the materials is 4:1. The above mixture is ground at a grinding speed of 300 r / min for 120 min to obtain a viscous slurry;

[0052] S2: drying the above viscous slurry in an oven at 103-105° C. to constant weight to obtain a dry slurry;

[0053] S3: The dried slurry was calcined in air for 3 hours at a calcination temperature of 400°C. After calcination, it was naturally cooled to room temperature to obtain Ru@TiZrOx-Ov-4 lattice oxygen-regulated nanocatalyst. The electron microscopy results showed that the average diameter of the active metal nanoparticles was 2.0nm. XPS detection of the catalyst O1S showed that the proportion of lattice oxygen on the catalyst surface was greater than the proportion of defective oxygen. The deconvolution calculation results of the O1s XPS peak showed that lattice oxygen accounted for 63.4%, defective oxygen accounted for 35.8%, and the remaining 0.8% was oxygen-containing functional groups on the catalyst surface.

[0054] Example 5

[0055] The lattice oxygen-regulated nanocatalyst Ru@TiZrOx-Ov-5 is prepared by solid phase grinding method, comprising the following steps:

[0056] S1: Add a certain proportion of metal Ru and TiO into the ball mill 2 Nitrate and ZrO 2 Nitrate (TiZr / Ru molar ratio = 1:1), Ru content is 5wt.%, titanium oxide and zirconium oxide ratio is 50%:50%, and auxiliary material citric acid is added at the same time. 2 Nitrate and ZrO 2 The mass ratio of the sum of the nitrates is 1:1. After adding the above materials, agate balls as grinding media are added, and the mass ratio of the grinding media to the materials is 4:1. The above mixture is ground at a grinding speed of 300 r / min for 120 min to obtain a viscous slurry;

[0057] S2: drying the above viscous slurry in an oven at 103-105° C. to constant weight to obtain a dry slurry;

[0058] S3: The dried slurry was calcined in air for 3 hours at a calcination temperature of 400°C. After calcination, it was naturally cooled to room temperature to obtain Ru@TiZrOx-Ov-5 lattice oxygen-regulated nanocatalyst. The electron microscopy results showed that the average diameter of the active metal nanoparticles was 2.0nm. XPS detection of the catalyst O1S showed that the proportion of lattice oxygen on the catalyst surface was greater than the proportion of defective oxygen. The deconvolution calculation results of the O1s XPS peak showed that lattice oxygen accounted for 55.6%, defective oxygen accounted for 34.2%, and the remaining 10.2% were oxygen-containing functional groups on the catalyst surface.

[0059] Example 6

[0060] The lattice oxygen-regulated nanocatalyst Ni@TiZrOx-Ov-1 is prepared by solid phase grinding method, which includes the following steps:

[0061] S1: A certain proportion of metal Ni and TiO are added into the ball mill. 2 Nitrate and ZrO 2Nitrate (TiZr / Ni molar ratio = 10:1), Ni content is 2wt.%, titanium oxide and zirconium oxide ratio is 50%:50%, and auxiliary material citric acid is added at the same time. 2 Nitrate and ZrO 2 The mass ratio of the sum of the nitrates is 2.5:1. After adding the above materials, agate balls as grinding media are added, and the mass ratio of the grinding media to the materials is 4:1. The above mixture is ground at a grinding speed of 400 r / min for 120 min to obtain a viscous slurry;

[0062] S2: drying the above viscous slurry in an oven at 103-105° C. to constant weight to obtain a dry slurry;

[0063] S3: The dried slurry was calcined in air for 3 hours at a calcination temperature of 550°C. After calcination, it was naturally cooled to room temperature to obtain the Ni@TiZrOx-Ov-1 lattice oxygen-regulated nanocatalyst. The electron microscopy results showed that the average diameter of the active metal nanoparticles was 2.0nm. XPS detection of the catalyst O1S showed that the proportion of lattice oxygen on the catalyst surface was less than the proportion of defective oxygen. The deconvolution calculation results of the O1s XPS peak showed that lattice oxygen accounted for 30.6%, defective oxygen accounted for 53.1%, and the remaining 16.3% were oxygen-containing functional groups on the catalyst surface.

[0064] 1. Performance test:

[0065] Evaluate catalyst effects and reaction conditions through laboratory tests

[0066] 1. Laboratory test device: Figure 2 The 200 mL fixed bed reactor (model: CWAO-DA480) shown was developed by the Dalian Institute of Chemical Physics, Chinese Academy of Sciences. The process can be scaled up proportionally;

[0067] 2. The pilot test process is as follows: first, the catalyst is put into the reactor, and then the remaining sludge is transported to the fixed bed reactor through a high-pressure sludge pump, air is introduced into the reactor through an air delivery unit (a selection valve, a pressure relief valve, and a gas flow regulating valve are provided on the air delivery pipeline), and the heat source required for the reaction is provided to the reactor through a heating furnace. The catalyst and the remaining sludge undergo hydrolysis and oxidation reactions in the reactor, and the material obtained after the reaction is cooled by a heat exchanger, and the cooled solid-liquid mixture enters a sample storage tank, and finally the solid-liquid mixture in the sample storage tank is separated and filtered by a solid-liquid separation unit, and the supernatant obtained is the carboxylic acid carbon source;

[0068] 3. Catalyst evaluation method: The lattice oxygen-regulated nanocatalyst prepared in Examples 1 to 6 was used to treat the residual sludge, and the reaction without adding the catalyst was used as the control group. The catalyst evaluation test was performed in the HTO laboratory test. 200 mL of catalyst was added, and the sludge pump was used for sampling. Air was introduced as an oxidant. The reaction temperature was set to 180°C, the reaction pressure was set to 2.0 MPa, and the reaction contact time was set to 1.0 h (volume space velocity 1.0 h -1 ) After the first 8 hours of sample release, samples were taken every 6 hours. Each condition was sampled 3 times and the results were averaged.

[0069] Catalyst evaluation result analysis method: After the reaction, the sample was filtered, and the supernatant was tested for soluble COD using the national standard method and VFAs using high performance liquid chromatography; the mud cake was tested for moisture content, TS, and VS. The sample was refrigerated and stored at 4°C.

[0070] 4. Catalyst evaluation results:

[0071] The Ru@TiZrOx-Ov-1 catalyst prepared in Example 1 treated the residual sludge. After HTO treatment, the COD of the sludge pyrolysis liquid was 12549 mg / L. Acetic acid 234 mg / L (COD 261.1 mg / L), propionic acid 2245 mg / L (COD 3394 mg / L), butyric acid 2549 mg / L (COD 4628.5 mg / L), and valeric acid 1212 mg / L (COD 2468.2 mg / L) were detected in the pyrolysis liquid. The COD contribution of carboxylic acids accounted for 85.7%, of which C4-C5 carboxylic acids accounted for 56.6%. The filter cake VS / TS after HTO treatment decreased from 0.69 to 0.16, indicating that the catalyst can improve the degradation of sludge extracellular polymers, so that more organic matter in the sludge enters the sludge liquid phase, and the sludge is more thoroughly broken. At the same time, the released organic matter is mainly catalytically oxidized to C4-C5 carboxylic acids.

[0072] The Ru@TiZrOx-Ov-2 catalyst prepared in Example 2 was used to treat residual sludge. The COD of the sludge pyrolysis liquid after HTO treatment was 11497 mg / L. Formic acid 315 mg / L (109.5 mg / L), acetic acid 2789 mg / L (COD 2972.2 mg / L), propionic acid 1798 mg / L (COD 2718.2 mg / L), butyric acid 1879 mg / L (COD 3411.9 mg / L), valeric acid 577 mg / L (COD1175.1 mg / L) were detected in the pyrolysis liquid. The COD contribution of carboxylic acids accounted for 90.3%, of which C4-C5 carboxylic acids accounted for 39.9% of the COD, and C1-C2 carboxylic acids accounted for 26.8% of the COD. The VS / TS of the filter cake after HTO treatment dropped from 0.69 to 0.14, indicating that the catalyst can improve the degradation degree of extracellular polymers in the sludge, allowing more organic matter in the sludge to enter the sludge liquid phase, and the sludge is broken more thoroughly. At the same time, the released organic matter is mainly catalytically oxidized to C2~C5 carboxylic acids.

[0073] The Ru@TiZrOx-Ov-3 catalyst prepared in Example 3 treated the residual sludge. After HTO treatment, the COD of the sludge pyrolysis liquid was 10194 mg / L. Oxalic acid 1890 mg / L (COD 335.9 mg / L), formic acid 2854 mg / L (COD 992.0 mg / L), acetic acid 5667 mg / L (COD 6039.2 mg / L), propionic acid 789 mg / L (COD 1192.8 mg / L) were detected in the pyrolysis liquid. The COD contribution of carboxylic acids accounted for 84.0%, and the COD contribution of C1-C2 carboxylic acids accounted for 86.1%. The filter cake VS / TS after HTO treatment decreased from 0.69 to 0.11, indicating that the catalyst can improve the degradation degree of sludge extracellular polymers, so that more organic matter in the sludge enters the sludge liquid phase, and the sludge is more thoroughly cracked. At the same time, the released organic matter is catalytically oxidized to C1-C2 carboxylic acids.

[0074] The Ru@TiZrOx-Ov-4 catalyst prepared in Example 4 treated the residual sludge. After HTO treatment, the COD of the sludge pyrolysis liquid was 7935 mg / L. Acetic acid 997 mg / L (COD 1062.5 mg / L), propionic acid 1457 mg / L (COD 2202.7 mg / L), butyric acid 869 mg / L (COD 1577.9 mg / L), and valeric acid 776 mg / L (COD 1580.3 mg / L) were detected in the pyrolysis liquid. The COD contribution of carboxylic acids accounted for 81.0%, of which C4-C5 carboxylic acids accounted for 58.85%. The filter cake VS / TS after HTO treatment decreased from 0.69 to 0.16, indicating that the catalyst can improve the degradation of sludge extracellular polymers, so that more organic matter in the sludge enters the sludge liquid phase, and the sludge is more thoroughly cracked. The released organic matter is mainly catalytically oxidized to C4-C5 carboxylic acids.

[0075] The Ru@TiZrOx-Ov-5 catalyst prepared in Example 5 treated the residual sludge. After HTO treatment, the COD of the sludge pyrolysis liquid was 5886 mg / L. Acetic acid 587 mg / L (COD 625.6 mg / L), propionic acid 426 mg / L (COD 644.0 mg / L), butyric acid 1129 mg / L (COD 2050.0 mg / L), and valeric acid 784 mg / L (COD 1596.6 mg / L) were detected in the pyrolysis liquid. The COD contribution of carboxylic acids accounted for 83.5%, of which C4-C5 carboxylic acids accounted for 78.4%. The filter cake VS / TS after HTO treatment decreased from 0.69 to 0.11, indicating that the catalyst can improve the degradation of sludge extracellular polymers, so that more organic matter in the sludge enters the sludge liquid phase, and the sludge is more thoroughly broken. At the same time, the released organic matter is mainly catalytically oxidized to C4-C5 carboxylic acids.

[0076] The Ni@TiZrOx-Ov-1 catalyst prepared in Example 6 treated the residual sludge. After HTO treatment, the COD of the sludge pyrolysis liquid was 4469 mg / L. Oxalic acid 2781 mg / L (COD 494.2 mg / L), formic acid 978 mg / L (COD 339.9 mg / L), and acetic acid 3388 mg / L (COD 3610.5 mg / L) were detected in the pyrolysis liquid. The COD contribution of carboxylic acids accounted for 99.5%, all of which were C1-C2 monocarboxylic acids and dicarboxylic acids. The VS / TS of the filter cake after HTO treatment dropped from 0.69 to 0.10, indicating that the catalyst can improve the degradation degree of sludge extracellular polymers, so that more organic matter in the sludge enters the sludge liquid phase, and the sludge is more thoroughly cracked. The released organic matter is mainly catalytically oxidized to C1-C2 carboxylic acids.

[0077] In the control group, after 97% of municipal sludge was treated with HTO without the addition of lattice oxygen-regulated nanocatalyst, the COD of the sludge pyrolysis liquid was 8339 mg / L, and oxalic acid 20.1 mg / L, pyruvic acid 13.4 mg / L, glycolic acid 585.2 mg / L, formic acid 262.3 mg / L, acetic acid 316.9 mg / L, propionic acid 1165.9 mg / L, butyric acid 653.8 mg / L, isovaleric acid 214 mg / L were detected, and the contribution of carboxylic acid COD accounted for 50.4%. After the reaction, the sludge VS / TS dropped from 0.69 to 0.59.

[0078] Therefore, compared with the control group, the catalyst prepared by Examples 1-6 of the present invention can greatly improve the efficiency of sludge breakdown and hydrolysis reactions by treating residual sludge through metal sites coordinated with active nano-metal particles, and the sludge breakdown effect is better. It can also release organic matter and mainly catalytically oxidize it into C2~C4 carboxylic acids, which is convenient for resource utilization.

[0079] 5. Reaction condition evaluation method: Take the Ru@TiZrOx-Ov-1 catalyst prepared in Example 1 for HTO test, and carry out HTO test in the above-mentioned 10-hour device to examine the reaction temperature (140-200°C), reaction pressure (1.0-5.0MPa), reaction contact time (volume space velocity 0.5-2.0h -1 )’s impact.

[0080] Reaction condition evaluation result analysis method: After the reaction, the sample was filtered, and the supernatant was tested for soluble COD using the national standard method and VFAs using high performance liquid chromatography; the mud cake was tested for moisture content, TS, and VS. The sample was refrigerated and stored at 4°C.

[0081] 6. Reaction condition evaluation results:

[0082] (1) Effect of reaction pressure

[0083] Reaction temperature 180℃, reaction contact time 1.0h (volume space velocity 1.0h -1 ), the reaction pressure was set to 1.0MPa, 2.0MPa, 3.0MPa, 4.0MPa, and 5.0MPa, respectively, and the results are as follows:

[0084]

[0085] From the above results, it can be seen that within the range of 1.0-5.0MPa, the sludge is well broken down, the organic matter is well released, and more than 80% of the pollutants are converted into carboxylic acid products, which is beneficial for subsequent application as a carbon source. The increase in reaction pressure is beneficial to the deep breakdown of sludge and the removal of organic pollutants, which is beneficial to reducing the VS / TS of sludge after treatment and improving the degree of stabilization. However, with the increase in pressure, the oxidation capacity is enhanced, and the degree of complete mineralization of pollutants becomes higher, resulting in a decrease in the proportion of carboxylic acid COD in the pyrolysis solution.

[0086] (2) Effect of reaction temperature

[0087] Reaction pressure 2.0MPa, volume space velocity 1.0h -1 , the reaction temperatures were set at 140°C, 160°C, 180°C, and 200°C, respectively. The results are as follows:

[0088]

[0089] From the above results, it can be seen that within the range of 140℃~200℃, the sludge is well broken down, the organic matter is well released, and more than 80% of the pollutants are converted into carboxylic acid products, which is beneficial for subsequent application as a carbon source. The increase in reaction temperature is conducive to the deep breakdown of sludge and the removal of organic pollutants, which is beneficial to reducing the VS / TS of sludge after treatment and improving the degree of stabilization. However, as the temperature increases, the oxidation capacity increases, and the degree of complete mineralization of pollutants increases, resulting in a decrease in the proportion of carboxylic acid COD in the pyrolysis solution.

[0090] (3) Effect of reaction contact time

[0091] The reaction pressure was 2.0 MPa, the reaction temperature was 180°C, and the volumetric space velocity was set to 0.5 h -1 , 1.0h -1 , 2.0h -1 , that is, the reaction contact time is 2.0, 1.0, and 0.5h, and the results are as follows:

[0092]

[0093] From the above results, it can be seen that within the range of 0.5-2.0h reaction contact time, the sludge is well broken down, the organic matter is well released, and more than 80% of the pollutants are converted into carboxylic acid products, which is beneficial for subsequent application as a carbon source. The extension of the reaction contact time is beneficial to the deep breakdown of the sludge and the removal of organic pollutants, which is beneficial to reduce the VS / TS of the sludge after treatment and improve the degree of stabilization. However, as the contact time increases, the degree of oxidation becomes deeper, and the degree of complete mineralization of pollutants becomes higher, resulting in a decrease in the proportion of carboxylic acid COD in the pyrolysis solution. A shorter reaction contact time will lead to incomplete sludge breakdown, resulting in a higher VS / TS.

[0094] 2. Process testing:

[0095] The process of the process test of using the lattice oxygen-regulated nanocatalyst prepared by the present invention to treat excess sludge and simultaneously prepare a carboxylic acid carbon source is as follows:

[0096] like Figure 1 The figure shows the structure of the device used when the catalyst prepared by the present invention is used to treat excess sludge. The reaction tower 2 is connected to the heat exchange unit 3, the heat exchange unit is connected to the solid-liquid separation unit 4, the heat supply unit 1 (boiler) is connected to the reaction tower 2, and the heat exchange unit 3 is connected to the heat supply unit 1 (boiler); firstly, the catalyst is put into the reaction tower of the device, the excess sludge is transported to the reaction tower through the biological material transport unit, air is introduced into the reaction tower through the air transport unit, the heat source required for the reaction is provided to the reaction tower through the heat supply unit, and the catalyst and the excess sludge undergo a hydrothermal oxidation reaction. The remaining sludge is effectively broken down. The material obtained after the reaction is cooled by the heat exchange unit. The heat generated by the cooling of the reactants is recovered by the heat exchange unit and transported to the heat supply unit to achieve heat recovery and circulation. The cooled material is separated by the solid-liquid separation unit, and the supernatant obtained is the carboxylic acid carbon source, which can be used as a composite carbon source in the process of sewage treatment to achieve resource utilization. The main inorganic components of the solid mud cake obtained are oxides of silicon, aluminum, calcium, iron, etc. and trace heavy metals, which can be used as inorganic fillers for packaging cardboard, and can also be fired into ceramsite and catalysts for further resource utilization.

[0097] The Ru@TiZrOx-Ov-3 catalyst prepared in Example 3 was selected. Figure 1 In the process shown, the process test of HTO resource treatment of municipal sludge was carried out, the reaction temperature was 180°C, the reaction pressure was 2.0MPa, the reaction contact time was 1.0h, and the sewage treatment plant sludge was treated in situ (sludge moisture content 98%±1%). Because the properties of daily sludge (such as pollution degree, distribution of pollutants contained, etc.) changed according to the actual daily sewage treatment conditions, the VS / TS of the treated sludge was between 0.10 and 0.16, and the COD of the pyrolysis liquid was above 10000mg / L and below 15000mg / L, of which carboxylic acid products accounted for more than 80%, up to 99%, and the main products were C1~C2 monoacids and diacids.

[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lattice oxygen-regulated nanocatalyst, characterized in that: The lattice oxygen-regulated nanocatalyst comprises a carrier with a controllable ratio of lattice oxygen to defective oxygen and an active nanometal; The carrier is a composite oxide of TiO2 and ZrO2 with adjustable lattice oxygen ratio; The active nanometal is selected from any one of Ru and Ni active metal nanoparticles.

2. The lattice oxygen-regulated nanocatalyst according to claim 1, characterized in that: The active nano-metal loading is 0.5-5 wt.%.

3. The lattice oxygen-regulated nanocatalyst according to claim 1, characterized in that: The mass ratio of the two oxides TiO2 and ZrO2 in the carrier is 2:8 to 8:2; The metal molar ratio of the sum of Ti and Zr in the active nano-metal and the carrier composite oxide is 1:1-20.

4. A method for preparing a lattice oxygen-regulated nanocatalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Add active nano-metals and nitrates containing metal oxide TiO2 and nitrates containing metal oxide ZrO2 into a ball mill, wherein the molar ratio of the sum of the moles of Ti and Zr to the active nano-metal is 1 to 20:1; then add auxiliary materials, wherein the mass ratio of the auxiliary materials to the sum of the nitrates containing metal oxide TiO2 and the nitrates containing metal oxide ZrO2 is 1 to 2.5:1, and add grinding media at a mass ratio of grinding media to materials of 2 to 5:1 for grinding to obtain a viscous slurry; S2: drying the viscous slurry obtained in S1 in an oven at 103-105° C. to a constant weight to obtain a dry slurry; S3: calcining the dry slurry obtained in S2 in air, and naturally cooling to room temperature after calcination to obtain a lattice oxygen-regulated nanocatalyst.

5. The preparation method according to claim 4, characterized in that: The auxiliary material is solid organic acid.

6. The preparation method according to claim 4, characterized in that: In S1, the grinding medium is agate balls, the grinding speed is 200-500 r / min, and the grinding time is 60-180 min.

7. The preparation method according to claim 4, characterized in that: In S3, the dried slurry is calcined for 2 to 4 hours at a temperature of 400 to 700°C.

8. Use of a lattice oxygen-regulated nanocatalyst as described in any one of claims 1 to 3 or a lattice oxygen-regulated nanocatalyst prepared by the preparation method as described in any one of claims 4 to 7 in treating sludge to produce carboxylic acid carbon sources.

9. The use according to claim 8, characterized in that: The application is carried out in a device for hydrothermal oxidation of excess sludge, the device for hydrothermal oxidation of excess sludge comprising a raw sludge transmission system, a reaction tower (2), a heat exchange unit (3) and a solid-liquid separation unit (4) connected in sequence; the reaction tower (2) is also connected to a heat supply unit (1) and an air delivery unit, and the heat exchange unit (3) is connected to the heat supply unit (1); The process steps of the application are as follows: First, the residual sludge is transported to the reaction tower (2) by using a raw sludge transport system, and then the lattice oxygen-regulated nanocatalyst is added to the reaction tower (2). An oxidant is introduced into the reaction tower (2) through an air transport unit, and the reaction tower (2) is heated by using a heat supply unit (1). The lattice oxygen-regulated nanocatalyst catalyzes the residual sludge to undergo a hydrothermal oxidation reaction, whereby the residual sludge is decomposed and a carboxylic acid carbon source is generated. The solid-liquid mixture formed after the hydrothermal oxidation reaction is cooled by a heat exchange unit (3). After the cooling is completed, the solid-liquid mixture enters a solid-liquid separation unit (4) for solid-liquid separation, and the separated supernatant and filter cake resources are respectively collected.

10. The use according to claim 9, characterized in that: The conditions of the hydrothermal oxidation reaction are: reaction pressure 1.0-5.0 MPa, reaction temperature 140-200°C, volume space velocity 0.5-2.0 h -1 , the oxidant is oxygen in the air.